Grid-Stamping on a Polygon Model for Implementing Arbitrary-Shaped Boundary Conditions in a Moving Particle Semi-Implicit Method - Hee-Sung Shin; Jong-Chun Park (Journal of Marine Science and Engineering, 2023)
This study proposes a new wall boundary condition for the grid-stamping on a polygon (G-StoP) model, which enables a simpler and more efficient handling of boundary surfaces of arbitrarily complex-shaped bodies represented using polygons (or meshes). For example, computer-aided design surface data can be used to analyze flow using a particle-based fluid-solver moving particle semi-implicit method. For coupling simulations of fluid–multibody dynamics, the Pusan-National-University-modified MPS method is improved, and the coupling analysis is performed using RecurDyn, a commercial software package for multibody (or flexible multibody) dynamics. To confirm the applicability of the developed G-StoP model, hydrostatic pressure simulations are conducted in a rectangular tank at various corner angles. Then, the hydrostatic pressure results are compared with previously proposed polygonal wall boundary model results and theoretical solutions. That is, in the case with a corner angle of 30°, it was confirmed that the relative error to the experiment of the polygon model was 11.3%, while that of the G-StoP model was 1.3%. This demonstrates that the proposed G-StoP model is exceptional for numerical stability and robustness even when it is difficult to secure information on neighboring particles as the corner angle of the object becomes small. In addition, the G-StoP model was applied to dam breaking, subaerial landslide tsunami, and wine sloshing problems, and its accuracy and applicability were tested through comparison with experimental and other simulation results. As a result, it was shown that the present simulation results were much closer to the experiments than other simulations.